2007
DOI: 10.1021/ol701639u
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Chiroptical Molecular Switches Based on the Redox-Induced Conformational Changes

Abstract: A series of optically active bis(catecholketal)s 1-3 were prepared, and their chiroptical properties were investigated experimentally and theoretically, demonstrating that they undergo conformational changes upon 1-e(-) oxidation and can be used as redox-responsive chiroptical molecular switches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…1B). [29][30][31][32][33][34] Here, we report a new approach based on the intermolecular dimerization 35 of a pyridinium helicene that achieves strong, reversible chiroptical redox switching with a prominent 4500 mV hysteresis (see Fig. 1C and 2).…”
mentioning
confidence: 89%
“…1B). [29][30][31][32][33][34] Here, we report a new approach based on the intermolecular dimerization 35 of a pyridinium helicene that achieves strong, reversible chiroptical redox switching with a prominent 4500 mV hysteresis (see Fig. 1C and 2).…”
mentioning
confidence: 89%
“…Nevertheless, no TTF derivative is reported that shows a sign reversal in the maximum of an ECD spectrum without a shi in the wavelength. Apart from TTF derivatives, chiroptical switching via a redox process can be achieved with catechol, 65 viologen, 66 and tetraarylethylene 67 building blocks. Intense switching with a sign reversal was also observed for a viologentype dicationic helquat.…”
Section: Enantiomer Separation On Chiral Hplc and CD Spectroscopymentioning
confidence: 99%
“…The most well known of these involve the use of redox active catenanes, [5][6][7][8] metal coordination compounds, [9][10][11][12][13][14][15] rotaxanes, [11,12,14,[16][17][18][19][20][21][22] π-systems, [23][24][25][26][27][28] and crowded alkenes [29]. These systems are finding increasing application in solid-state electronic devices.…”
Section: Open Accessmentioning
confidence: 99%